Assessing security of cloud services in Malaysian universities a review - Mohamad, F.S.; Albahaloul, H.A. (2018)
Currently, The cloud computing emerged due to developing rapidly of technology, an Internet-based development in which dynamically scalable and often virtualized resources are provided as a service over the Internet, universities are reviewing IT services and considering common service options. Studies suggest that a wide range of IT services can be shared in higher education that offer several potential features .Nowadays, the security of information becomes more substantial. The aim of this paper analyzes the security issue in cloud computing and review the effect of cloud data privacy on the transition to the cloud computing system in the Malaysian Universities.